기능적 의사소통 중재(FCT)가 발달지체 유아의 대체행동과 문제행동에 미치는 영향 - 김효정(Kim, Hyo Jeong); 김은경(Kim, Eun Kyung) (특수교육논총, 2021)
연구목적: 이 연구에서는 기능적 의사소통 중재가 발달지체 유아의 대체행동과 문제행동에 미치는 영향을 알아보았다. 연구방법: 연구대상은 어린이집의 통합학급에 재학 중인 만 4세 발달지체 유아 1명이며 중재는 개별 언어치료실에서 시행되었다. 실험설계로 행동간 중다간헐기초선 설계를 적용하였고 연구는 기초선, 중재, 유지 단계로 진행되었다. 기능평가를 통해 세 가지 문제행동의 기능을 파악하고 세 가지 행동의 기능적 독립성을 확인하였다. 문제행동에 대한 대체의사소통 행동을 선정하고 이를 기능적 의사소통 중재를 통해 지도하였다. 연구결과: 기능적 의사소통 중재를 통해 발달지체 유아의 대체행동의 발생 빈도가 증가되고 문제행동의 발생 빈도는 감소되었다. 또한 중재 효과는 중재 종료 후에도 유지되었다. 결론: 이 연구의 결과는 문제행동의 의사소통 기능을 파악하여 이에 따른 대체행동을 지도한 기능적 의사소통 중재가 발달지체 유아의 대체행동 향상과 문제행동 감소에 영향을 미칠 수 있음을 시사한다. Purpose: The purpose of the study was to investigate the effect of functional communication training on the alternative communication behaviors and challenging behaviors of a preschooler with developmental delays. Method: The participant was a four-year-old preschooler with developmental delays who was enrolled in a special class in kindergarten and participated in an individual speech therapy class. A multiple–probe baseline across behaviors was used as for the research design. The study was carried out in the following order: baseline assesment, intervention, and maintenance. Alternative behaviors were selected based on a functional behavior assessment. The functional communication training was implemented by instructing the subject in alternative communication behaviors. Result: The functional communication training was effective for increasing the subject’s alternative communication behavior and decreasing the challenging behavior of the preschooler with developmental delays in the study. The effect of the intervention was maintained in the follow-up phase. Conclusion: The results of this study suggest that functional communication training in alternative behaviors based on the communication functions of problematic behaviors increases alternative communication behaviors and decreases the challenging, problematic behaviors of a preschooler with developmental delays. KCI Citation Count: 1